2014
DOI: 10.1161/strokeaha.113.004296
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Intracellularly Accumulated Zinc Decreased Ischemic Brain Injury Through Reducing Neuronal Apoptotic Death

Abstract: Background and Purpose-Zinc has been reported to possess both neurotoxic and neuroprotective capabilities. The effects of elevated intracellular zinc accumulation following transient focal cerebral ischemia remain to be fully elucidated. Here, we investigated whether removing zinc with the membrane-permeable zinc chelator, N,N,Nʹ,Nʹ-tetrakis(2-pyridylmethyl) ethylenediamine (TPEN), would decrease the intracellular levels of zinc in the ischemic tissue, leading to reduced brain damage and improved neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 25 publications
4
52
0
1
Order By: Relevance
“…The latter finding is consistent with previous studies demonstrating that PARP-1 enzymatic activity is increased after ischemia, although PARP-1 protein expression is not altered (Hu et al, 2013;Nagayama et al, 2000;Zhao et al, 2014). The activation of PARP-1 after ischemia may be relevant to the subsequent neurovascular deficits.…”
Section: Discussionsupporting
confidence: 92%
“…The latter finding is consistent with previous studies demonstrating that PARP-1 enzymatic activity is increased after ischemia, although PARP-1 protein expression is not altered (Hu et al, 2013;Nagayama et al, 2000;Zhao et al, 2014). The activation of PARP-1 after ischemia may be relevant to the subsequent neurovascular deficits.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to findings of a previous study that found zinc supplementation reversed diabetes-induced cardiac and renal oxidative damage, inflammation, and fibrosis [18]. In another study, cerebral ischaemia caused dramatic cytosolic zinc accumulation in ischaemic tissue that was reduced markedly by 15 mg∙kg −1 TPEN pretreatment [27]. In our study, IH did not cause zinc accumulation in the LV.…”
Section: Discussionsupporting
confidence: 92%
“…Each group was further subdivided into three groups that received i.p. injections of vehicle (Veh; a mix of ethanol: glycerol: H 2 O in the ratio 1:3:6; n = 5) [26], zinc chloride (Zn; 10 mg∙kg -1 ; n = 5), or the membrane-permeable zinc chelator N,N,N',N'-tetrakis(2-pyridylmethyl) ethylenediamine (TPEN; 5 mg∙kg -1 , n = 5) [18, 27]. The injections were administered to IHCON and IHEXE rats 30 min before IH exposure.…”
Section: Methodsmentioning
confidence: 99%
“…12 However, contradictory studies indicate that at 7 days post-TBI Zn chelation is associated with an upregulation of neuroprotective genes in rat brain, 13 and a 14-day Zn chelation trial in rat cerebral ischemia was associated with reduced neuronal apoptosis. 14 However, these studies were performed in younger animals, and their relevance to aged animals, where there is increased risk of negative outcomes following TBI, remains unknown. There have been two human clinical trials assessing the therapeutic roles of Zn post-TBI, 15 both of which have had significant positive patient outcomes.…”
Section: Introductionmentioning
confidence: 99%